Design of a knowledge management tool for mastery of Finnish professional vocabulary: An application of Nam Suh's axiomatic design principles - Mbi, Bate Eya (My University, 2017)
A language component which is very absent in the lecture-composition of integration programmes in Finland, is the teaching of Finnish professional vocabulary. This gap leads to a very pertinent issue of poorly equipped immigrants: with respect to the mastery and use of Finnish professional vocabulary. From a suggestive perspective, this problem can negatively influence Finland's integration efforts and leads to the waste of valuable resources. The aim of this thesis is to solve this problem from technology perspectives and by applying design thinking. To address this problem, this thesis applied the principles of axiomatic design. This thesis identified a set of stakeholders and customer attributes (CA). Most CAs were identified from a reputable secondary source and thus, increasing the designed solution´s reliability. With respect to the research problem and identified CAs, axiomatic design was applied to generate an original solution, framed on the learning loops concepts. Due to the exploratory nature of the applied design technique: axiomatic design, this thesis is both exploratory and applied. The result of this research is a conceptual solution: a knowledge management tool that enables immigrants to learn independently and master relevant Finnish professional vocabulary. The solution is an information and communication technology (ICT) - based tool that can positively affect masses. Its prime value is that it can contributes to employee empowerment and boost integration in Finland. Finally, the designed solution is systemic in nature and due to this, the solution is graphically demonstrated with reference to a sample use case process. The graphical illustrations: mock-ups, demonstrate and justify the main design choices, as well as illustrate the solution´s sample applicability.
Keywords: Axiomatic design; Finnish professional vocabulary; knowledge management; product development.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|